Stiff “Left Atrial” syndrome post-mustard procedure - Cowgill, Joshua A; Moran, Adrian M (Journal of Cardiology and Cardiovascular Medicine, 2021)
Objectives: We describe the clinical course and management of two patients with post-capillary pulmonary hypertension due to diffuse pulmonary venous baffle calcification decades post-Mustard procedure. Background: From the late 1950s to the early 1990s, the definitive surgical repair for children with D-transposition of the great vessels (D-TGA) was an atrial switch procedure (either Senning or Mustard operation) which utilizes atrial-level baffles to shunt pulmonary venous blood to the morphologic right (systemic) ventricle and caval blood to the morphologic left (sub-pulmonary) ventricle. From a hemodynamic standpoint, baffle leaks and stenoses as well as precapillary pulmonary hypertension have all been described as both early and late complications [1]. Recently, delayed post-capillary pulmonary hypertension (in the absence of discrete baffle obstruction) decades post-atrial switch has also been described [2]. The underlying pathophysiology for this postcapillary pulmonary hypertension is unclear but is theorized to involve impaired diastology referable to the pulmonary venous baffle. Methods/Results: Using hemodynamic and imaging data, we describe two patients with extensive pulmonary venous baffle calcification and resultant pulmonary hypertension from the so-called “stiff left atrial (LA) syndrome.” This problem can be difficult to treat medically and is not amenable to catheter-based interventions. We hypothesize that this is an underlying mechanism for pulmonary hypertension in at least some post-Mustard and Senning patients. Conclusion: We describe the treatments and clinical course for each of these patients, and in particular describe how the surgical revision of the pulmonary venous baffle in one case led to the complete resolution of symptoms.